2017
DOI: 10.1007/s10695-017-0371-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and fatigue on the metabolism and swimming capacity of juvenile Chinese sturgeon (Acipenser sinensis)

Abstract: Chinese sturgeon (Acipenser sinensis) is a critically endangered species. A flume-type respirometer, with video, was used to conduct two consecutive stepped velocity tests at 10, 15, 20, and 25 °C. Extent of recovery was measured after the 60-min recovery period between trials, and the recovery ratio for critical swimming speed (U ) averaged 91.88% across temperatures. Temperature (T) effects were determined by comparing U, oxygen consumption rate (MO ), and tail beat frequency (TBF) for each temperature. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
0
10
2
Order By: Relevance
“…As the success rate for migration through and/or over various fish barriers is likely limited by a fish's swimming performance, it is highly plausible that fish, including sturgeon, may require multiple attempts to traverse a fish passage structure (Cai et al ., ; Yuan et al ., ). Shortnose sturgeon, a relatively poor performing fish relative to other fish species, might not show consistent swimming performance patterns if they are forced to undergo multiple fatigue–recovery cycles.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…As the success rate for migration through and/or over various fish barriers is likely limited by a fish's swimming performance, it is highly plausible that fish, including sturgeon, may require multiple attempts to traverse a fish passage structure (Cai et al ., ; Yuan et al ., ). Shortnose sturgeon, a relatively poor performing fish relative to other fish species, might not show consistent swimming performance patterns if they are forced to undergo multiple fatigue–recovery cycles.…”
Section: Introductionmentioning
confidence: 97%
“…Cai et al (2014) found that the critical swimming (UCrit) speeds of sturgeon decreased~32% with successive recoveries from fatigue over four cycles (~19-20 C; trials were separated by 20 min). More recently, however, Yuan et al (2017) found that there were no differences in UCrit between swim trials 1 and 2 (separated by 60 min) across temperatures (10-25 C) for Chinese sturgeon. Thus, these differences suggest that the effects of repetitive swimming on the metrics of swimming performance are not clear, at least for sturgeon species, and further research is required.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…In an RAS, water temperature and ammonia nitrogen are two important environmental factors that affect the growth of the Chinese sturgeon (Du et al, ; Yuan et al, ). It is found that higher water temperatures (up to 20°C) may have beneficial effects in maximizing growth and improving the immunological capacity of juvenile shortnose sturgeon ( Acipenser brevirostrum ) compared with a water temperature of 11°C, regardless of fish size (Gradil et al, ).…”
Section: Introductionmentioning
confidence: 99%